Illustrating where spatial perception versus memory-based representation: spatial neglect in a distinguished artist; a case report. Issue 3 (4th May 2018) - Hreha, Kimberly; Chaudhari, Amit; Kong, Yekyung; Maduri, Prathusha; Barrett, A.M.
ABSTRACT: Spatial neglect is a disorder of attention, perception, and processing of stimuli in contralesional space. The heterogeneous behaviors involve diverse neuroanatomical mechanisms. Anecdotal evidence suggests that neural circuitry of active spatial perception may differ from that used to encode spatial memory. These differences can escape detection by conventional assessments, thereby leading to missed diagnoses. We present a case, in an artist who demonstrates selective impairment in a contralesional space during active Where spatial perception. His performance is better when asked to draw entirely from memory. This case highlights the variability in neglect, importance for comprehensive testing, and encourages further investigation.